1999
DOI: 10.1128/iai.67.12.6670-6677.1999
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxins 1 and 2 Translocate Differently across Polarized Intestinal Epithelial Cells

Abstract: Shiga toxin-producing Escherichia coli (STEC) is an important food-borne pathogen that causes hemolytic-uremic syndrome. Following ingestion, STEC cells colonize the intestine and produce Shiga toxins (Stx), which appear to translocate across the intestinal epithelium and subsequently reach sensitive endothelial cell beds. STEC cells produce one or both of two major toxins, Stx1 and Stx2. Stx2-producing STEC is more often associated with disease for reasons as yet undetermined. In this study, we used polarized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…This represents a profound fundamental difference that could have major significance in the differing pathogenicity of EHEC in these hosts. Although human intestinal epithelium lacks Gb3, this remains an important interface with VT as in vitro studies (Philpott et al, 1997;Hurley et al, 1999) have shown that VT is actively transported across these cells without disrupting cellular integrity. VT is thereby delivered to the basal surface of the epithelium where it gains access to receptor-positive cells including endothelium (leading to vascular disruption) and macrophages (evoking inflammatory mediators).…”
Section: Discussionmentioning
confidence: 99%
“…This represents a profound fundamental difference that could have major significance in the differing pathogenicity of EHEC in these hosts. Although human intestinal epithelium lacks Gb3, this remains an important interface with VT as in vitro studies (Philpott et al, 1997;Hurley et al, 1999) have shown that VT is actively transported across these cells without disrupting cellular integrity. VT is thereby delivered to the basal surface of the epithelium where it gains access to receptor-positive cells including endothelium (leading to vascular disruption) and macrophages (evoking inflammatory mediators).…”
Section: Discussionmentioning
confidence: 99%
“…Caco‐2 and T84 epithelial cells were grown on collagen‐coated Transwell filter inserts (6.5 mm diameter, 0.4 µm pore size; Costar) as described previously (Hurley et al ., 1999), and TEER was monitored with an EVOM resistance reader (WPI). Cells were differentiated for 7–12 days until stable TEER values of 500 (Caco‐2) and 1800 (T84) Ω cm 2 were obtained indicating establishment of epithelial barrier function.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristic intestinal damage caused by STEC includes hemorrhage and edema in the lamina propria with focal necrosis and neutrophil infiltration. Recently, it was shown that Stx1 and Stx2 are translocated across polarized intestinal epithelial monolayers via transcellular and paracellular mechanisms [19,20]. In this manner, Stxs may gain access to and damage colonic blood vessels.…”
Section: Stxsmentioning
confidence: 99%
“…These cell types respond differently to Stxs. For example, T84 cells, a human intestinal epithelial cell line, lack the toxin glycolipid receptors and are not killed by Stxs in vitro, yet are capable of toxin translocation from apical to basolateral surfaces [19]. Bovine crypt intestinal epithelial cells, in contrast, express Gb 3 but escape killing by routing the toxins to lysosomes rather than to the ER [32].…”
Section: Stxs and Apoptosismentioning
confidence: 99%